FPGA Hardware Acceleration of AI Models for Real-Time Breast Cancer Classification - Ayoub Mhaouch; Wafa Gtifa; Mohsen Machhout (AI)
Breast cancer detection is a critical task in healthcare, requiring fast, accurate, and efficient diagnostic tools. However, the high computational demands and latency of deep learning models in medical imaging present significant challenges, especially in resource-constrained environments. This paper addresses these challenges by presenting an FPGA hardware accelerator tailored for breast cancer classification, leveraging the Zynq XC7Z020 SoC. The system integrates FPGA-accelerated layers with an ARM Cortex-A9 processor to optimize both performance and resource efficiency. We developed modular IP cores, including Conv2D, Average Pooling, and ReLU, using Vivado HLS to maximize FPGA resource utilization. By adopting 8-bit fixed-point arithmetic, the design achieves a 15.8% reduction in execution time compared to traditional CPU-based implementations while maintaining high classification accuracy. Additionally, our optimized approach significantly enhances energy efficiency, reducing power consumption from 3.8 W to 1.4 W a 63.15% reduction. This improvement makes our design highly suitable for real-time, power-sensitive applications, particularly in embedded and edge computing environments. Furthermore, it underscores the scalability and efficiency of FPGA-based AI solutions for healthcare diagnostics, enabling faster and more energy-efficient deep learning inference on resource-constrained devices.